Development of Authentic Assessment in Geometry Learning - Abd Kadir Jaelani; Muhammad Hasbi (JRPM (Jurnal Review Pembelajaran Matematika), 2022)
This study aims to describe the process and results of the development of authentic assessment in teaching geometry which refers to the 4-D model. Geometry authentic assessment in this study includes learning achievement tests, self-assessment, portfolio assessment, performance assessment guidelines, self-assessment guidelines, portfolio assessment guidelines, feasibility test instruments, teacher response questionnaires, student response questionnaires, and validation sheets. The research subjects are 8th-grade students of SMPN 2 Barombong, Gowa Regency. The validity test analysis is rationally obtained through two the results of the validation of experts, test reliability both rationally and empirically, and objectivity using the product-moment formula. The results showed that the authentic assessment met the criteria of being valid, practical, and effective. As a consequence, it is suggested that the development of authentic assessment tools for geometry learning be expanded to other resources to make teacher evaluation easier. Furthermore, the study's implications provide teachers with information for conducting authentic assessment formulation in the implementation of learning, especially for students.